Bifurcation analysis of stage-structured sea turtles' population with time delay / Nurul Syuhada' Halim and Nur Syazwina Tumiran - Halim, Nurul Syuhada'; Tumiran, Nur Syazwina (2022)
In this paper, we examine the sea turtle population’s time-delayed population dynamics. The population of sea turtles in Malaysia is declining, and they are one of the country’s endangered species, according to previous research. Additionally, the presence of temporal delay may cause population decline and oscillations in population persistence. So, in order to determine its equilibrium point, we conducted a stability analysis on a population of sea turtles with a delayed stage structure. It is discovered that it is asymptotically stable at the interior equilibrium. A Hopf bifurcation with delay as the bifurcation parameter has been carried out to examine the population’s response to time delay. It is discovered that Hopf bifurcation does not take place at the interior equilibrium point, indicating that no stability switch or bifurcation takes place for all delays. Numerical simulations were conducted to study the population’s behavior as a result of a time delay in order to corroborate the analytical results. The graph illustrated using MAPLE software support our findings.